Selection of soybean cultivars in the closed-pantanal eco-toon region (Research, Society and Development, 2020)
The objective of this work was to evaluate the performance of sixteen soybean cultivars and to indicate those with the best adaptation to the cultivation in the region of Aquidauana, MS. The work was carried out in the experimental area of the State University of Mato Grosso do Sul, Unit of Aquidauana, in the agricultural year 2014/2015, in conventional planting system. The experimental design was a completely randomized design with 16 treatments (RR: 97R21, 97R71, 97R73, 97Y07, AS3610, AS3730, AS3797, B4184, B4377, CD238, MOSOY6410, P98Y11, POWER, SYN1163, SYN13671 and SYN9070) . The plots consisted of seven lines with 5 m of length, with spacing of 0.45 m between rows and density of 15 plants per meter. The agronomic characteristics of plant height at maturity, height of first pod insertion, number of branches, number of pods per plant, number of grains per pods, mass of one hundred grains and grain yield were evaluated. After data collection, the Liliefors test was adjusted for error and the variance homogeneity was verified by the Bartlett test, and the data were submitted to analysis of variance and the grouping of means by the Skott-Knott test at 5% probability . It was concluded that the cultivar B4377 obtained the best performance by analyzing the variables AP, AIV, NR and NVP together. The cultivars that obtained the best performance by analyzing the variables NGV, MCG and PROD together were AS3730 and P98Y11. Plant height NVP and MCG did not influence the best grain yield. Considering grain yield, all evaluated materials may be recommended for the region.